Atherosclerosis Prediction with High Sensitivity C-Reactive Protein (hs-CRP) and Related Risk Factor in Patient with Dyslipidemia - Swastini, Dewa Ayu (Open Access Maced J Med Sci, 2019)
BACKGROUND: Inflammation plays a major role in the initiation, destabilization and the progression of atherosclerosis. High Sensitivity C-Reactive Protein (hs-CRP) reflects active systemic inflammation and have shown to be a strong predictor of future cardiovascular events. AIM: The purpose of this study was to determine the role of High Sensitivity C-Reactive Protein (hs-CRP) independent for atherosclerosis severity prediction and to find out which factors largely is affecting hs-CRP level in dyslipidemia patient. METHODS: A total of 388 patients (267 dyslipidemia, 121 controls) were enrolled in this study. We investigated whether plasma hs-CRP is associated with atherosclerosis severity that was quantified by ankle-brachial index (ABI) and Doppler ultrasound. Related risk factor that influence hs-CRP levels in patients with dyslipidemia included determination of age, gender, diabetes, smoking, hypertension, total cholesterol, TG, LDL, HDL, and fasting glucose. RESULTS: Data showed a significant association between hs-CRP concentration level and the severity of atherosclerosis (p < 0.01). Univariate analysis showed that fasting plasma glucose, triglyceride, and BMI were significantly positively correlated with hs-CRP levels. Whereas, HDL cholesterol was negatively correlated with hs-CRP levels. Multivariate regression analysis using model 1 and 2, showed that in determining hs-CRP levels, triglyceride and BMI were taking a big role. CONCLUSION: Hs-CRP correlates with extent of atherosclerosis, and high triglyceride and BMI is closely associated with high hs-CRP levels in patients with dyslipidemia.